CONCEPTUAL MODEL OF INTEGRATED INTERNATIONAL EDUCATIONAL ENVIRONMENT AS A FACTOR OF INCREASE IN EXPORT OF HIGHER EDUCATION SERVICES IN RUSSIAN FEDERATION - Elena Zashchitina (Вестник Северо-Кавказского федерального университета, 2022)
Today, universities are beginning to be considered as drivers of the development of territories, and the internationalization of higher education as an indicator of the competitiveness of the national education system. It is happening in the context of increasing attention to such trends in the development of the modern economy as competitiveness, innovation, productivity, knowledge economy and digital economy. This is also justified by the increase in the number of international students and, as a consequence, the volume of the world market of educational services. Thus, in the short term, it is necessary to build a conceptual model of integrated international educational environment on the basis of the analysis offactual and empirical data. It could be useful in building an effective policy in the field of export of educational services, within the main trends and imperatives that determine the choice of international students of the country of study.